2001
DOI: 10.1054/bjoc.2000.1620
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the Id3 gene at 1p36.1 in ovarian adenocarcinomas

Abstract: SummaryThe molecular events that drive the initiation and progression of ovarian adenocarcinoma are not well defined. We have investigated changes in gene expression in ovarian cancer cell lines compared to an immortalized human ovarian surface epithelial cell line (HOSE) using a cDNA array. We identified 17 genes that were under-expressed and 10 genes that were over-expressed in the cell lines compared to the HOSE cells. One of the genes under-expressed in the ovarian cancer cell lines, Id3, a transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…19 In this study, Id-3 staining was not significantly different between nodular hyperplasia and lowgrade prostate cancer (Figure 3c). However, we observed a significant decrease in expression of Id-3 in high-grade prostate cancer as compared to low-grade prostate cancer (Figure 3c).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…19 In this study, Id-3 staining was not significantly different between nodular hyperplasia and lowgrade prostate cancer (Figure 3c). However, we observed a significant decrease in expression of Id-3 in high-grade prostate cancer as compared to low-grade prostate cancer (Figure 3c).…”
Section: Discussionmentioning
confidence: 46%
“…Id-3 expression was reduced in ovarian cancer. 19 These results suggest that the expression of different Id proteins in different types of cancer could be used as prognostic markers of cancers.…”
mentioning
confidence: 93%
“…Transgene expression of ID1 and ID2 in mice has resulted in tumor formation in the intestinal epithelium and lymphoid organs, respectively (Wice and Gordon 1998; Morrow et al, 1999). Expression of ID3 has been more variable with studies reporting both upregulation (Wilson et al, 2001;Vandeputte et al, 2002) and downregulation (Arnold et al, 2001;Deleu et al, 2002) in different tumor types. Little is known, however, about the expression, regulation and potential roles of ID4 in the carcinogenic process.…”
mentioning
confidence: 99%
“…We previously conducted a screen for genes aberrantly expressed in three ovarian adenocarcinoma cell lines compared to an immortalised HOSE using a human cDNA array containing 588 known genes (Arnold et al, 2001a). This showed that expression of CCL2 is greatly reduced in ovarian cancer cell lines.…”
Section: Ccl2 Expression Analysis In Ovarian Adenocarcinoma Cell Linesmentioning
confidence: 99%
“…Using cDNA array screening of normal OSE cells and ovarian cancer cell lines, we previously identified CCL2 as a gene whose expression is downregulated or lost in ovarian cancer cell lines (Arnold et al, 2001a). In this report, we describe the characterisation of CCL2 expression in a larger panel of ovarian cancer cell lines and primary tumours and mutation analysis of the CCL2 gene in primary ovarian adenocarcinomas.…”
mentioning
confidence: 93%